Fluid–structure coupling analysis of impeller in unstable region for a reversible axial-flow pump device - Fan Meng (Advances in Mechanical Engineering, 2018)
Reversible axial-flow pump is widely adopted in the coastal regions or along the river. Due to severe vibration, which results in impeller cracks in unstable region, the fluid–structure interaction solving strategy of impeller was applied for reversible axial-flow pump. In unstable region, the two-way coupling method was employed to obtain the pump performance curve and the quantity analysis of deformation and stress on impeller. The results show that the measured efficiency and head are in good agreement with the simulation values. Under positive rotation, the maximum equivalent stress and total deformation are found to be below 0.75 Q des . Under negative rotation, the maximum total deformation is observed to be below 0.65 Q des and the maximum equivalent stress increases with increase in flow rate. Whether under positive or negative rotation, along the direction from impeller inlet to outlet and in the direction from impeller hub to rim, the total deformation goes up and the equivalent stress first increases and then declines. The results indicate that the equivalent stress reduces with decrease in fillet radii. The analysis results of deformation and stress can be utilized to guide the structure design of reversible axial-flow pumps and attain more stable pump performance.